Social Protest and Human Rights Education: Students on the Move - Franco Bautista, Karen Maricel (2025)
This article is part of a research process focused on teaching social protest in high schools, addressing the protests that took place in Colombia between 2019 and 2021, from the perspective of human rights education (HRE). The paper underscores the importance of this education to enable diverse relationships within academia, demonstrating the challenges of positioning this education in school and university spaces, as well as the ongoing tensions between theory, practice, and political training in schools. With this understanding, the research seeks to answer, among other questions, what happened to schools during the protests and how social mobilization impacted educational communities. To provide an answer, we employed a qualitative research approach, which facilitated the gathering of empirical data describing common and problematic moments through a multiple case study conducted in schools in Bogotá, Cali, and Medellín. The analysis of outcomes highlights the need to recognize how the social protests in Colombia between 2019 and 2021, also known as social outbursts, were, or were not, integrated into school and university contexts. This need is linked to the importance of HRE, citizen training, and the commitment to social transformation, understanding the fundamental role played by the young people, and how they either brought the classrooms to the streets or vice versa, as students mobilized for the defense and promotion of human rights. This demonstrates the necessity of incorporating human rights into primary, secondary, and higher education.